2001
DOI: 10.1016/s0022-5347(05)65549-8
|View full text |Cite
|
Sign up to set email alerts
|

Erectile Function After Anterior Urethroplasty

Abstract: Overall anterior urethral reconstruction appears no more likely to cause long-term postoperative sexual dysfunction than circumcision. Men with a long stricture may be at increased risk for transient erectile changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(81 citation statements)
references
References 10 publications
0
75
0
6
Order By: Relevance
“…These nerves occupy the 1 and 11 o'clock positions at the level of convergence of the crura of the corpora cavernosa. In addition, the corpus spongiosum is highly elastic and can be readily re-anastomosed after mobilization and stricture excision, even in cases of long strictures [8]. Taken together, these findings suggest that anterior urethral reconstruction should not predispose patients to long-term ED.…”
Section: Discussionmentioning
confidence: 88%
“…These nerves occupy the 1 and 11 o'clock positions at the level of convergence of the crura of the corpora cavernosa. In addition, the corpus spongiosum is highly elastic and can be readily re-anastomosed after mobilization and stricture excision, even in cases of long strictures [8]. Taken together, these findings suggest that anterior urethral reconstruction should not predispose patients to long-term ED.…”
Section: Discussionmentioning
confidence: 88%
“…Incidences in the range of 5-26% have been reported after anastomotic urethroplasty for anterior urethral strictures. 20,21 Interestingly Carlton et al 22 observed that the initial injury, not the reconstructive surgery, is responsible for most of the long-term ED.…”
Section: Discussionmentioning
confidence: 99%
“…Penile surgery created branches that pierced the tunica albuginea of the CS at 12 o'clock, risking injury during an internal urethrotomy (Mundy, 1993;Coursey et al 2001).…”
Section: Discussionmentioning
confidence: 99%